2007
DOI: 10.1021/jf061955p
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analytical Method for the Determination of Hydrophilic Metabolites by High-Performance Liquid Chromatography and Mass Spectrometry

Abstract: A method for the comprehensive analysis of hydrophilic metabolites, based on a combination of high-performance liquid chromatography and mass spectrometry, is described. We evaluated three types of stationary phases to achieve the separation of highly hydrophilic metabolites. Good chromatographic retention and separation of these metabolites were achieved on a pentafluorophenylpropyl-bonded silica column with gradient elution, using 0.1% aqueous formic acid and acetonitrile as the mobile phase. The optimized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 20 publications
0
54
0
Order By: Relevance
“…is is also because there has been no de nite and versatile inlet method that is able to simultaneously separate a wide variety of metabolites. In the case of LC/MS metabolomics, there are at least 5 groups of LC conditions, which include reverse phase analysis using octadecylsilyl (ODS) column for relatively hydrophobic metabolites, 45) normal phase analysis using columns for hydrophilic interaction chromatography (HILIC) of hydrophilic metabolites, [46][47][48] reverse phase analysis using pentafluorophenylpropyl stationary phase column for hydrophilic metabolites, 49) ion-paring methods using ODS column for anionic metabolites, 50) and lipidomics methods using ODS column for lipids. Recently, a comparison of the chromatographic performance of a traditional ODS column with various HILIC and mixed-mode columns showed that ODS and zwitterionic HILIC columns are the best combination for wide metabolite coverage.…”
Section: Bottleneck In the Metabolomics 2: Quantification Without Valmentioning
confidence: 99%
“…is is also because there has been no de nite and versatile inlet method that is able to simultaneously separate a wide variety of metabolites. In the case of LC/MS metabolomics, there are at least 5 groups of LC conditions, which include reverse phase analysis using octadecylsilyl (ODS) column for relatively hydrophobic metabolites, 45) normal phase analysis using columns for hydrophilic interaction chromatography (HILIC) of hydrophilic metabolites, [46][47][48] reverse phase analysis using pentafluorophenylpropyl stationary phase column for hydrophilic metabolites, 49) ion-paring methods using ODS column for anionic metabolites, 50) and lipidomics methods using ODS column for lipids. Recently, a comparison of the chromatographic performance of a traditional ODS column with various HILIC and mixed-mode columns showed that ODS and zwitterionic HILIC columns are the best combination for wide metabolite coverage.…”
Section: Bottleneck In the Metabolomics 2: Quantification Without Valmentioning
confidence: 99%
“…This was a weakness of LC-MS analysis, and LC-MS was limited to the analysis of hydrophobic metabolites such as lipids. However, the development of column technology enabled the retention and separation of hydrophilic metabolites (Alpert, 1990;Yoshida et al, 2007). This technology has been applied for the research of drug metabolites (Plumb et al, 2003), galactosamine toxicity (Spagou et al, 2011), and renal cell carcinoma diagnosis, staging, and biomarker discovery (Lin et al, 2011a).…”
Section: Analytical Issuesmentioning
confidence: 99%
“…T h e r e a r e s o m e a p p r o a c h e s w i t h o u t a n y derivatization of amino acids for MS detection coupled to capillary electrophoresis (11) or LC using a pentafluorophenylpropyl-bonded silica column (12) or a porous graphitic carbon column (13). Such highly sensitive AAA described above can complement MS-based proteomics of low abundance proteins.…”
Section: Introductionmentioning
confidence: 99%